Berberine in the treatment of radiation-induced skin injury: insights from proteomics and network pharmacology - Zou, Jie; Xiao, Xia-Juan; Zhang, Ping; Huang, Xing-Zi; Wang, Jing; Tao, Chun-Qin; Ou, Xiao-Lan; Chen, Gong; He, Ting-Hao; Yang, Long; Huang, Biao; Yu, Dao-Jiang; et al. (Frontiers in Pharmacology, 2025)
BackgroundRadiation-induced skin injury (RISI) is a notable complication of cancer radiotherapy, impacting patients’ quality of life. Existing interventions mainly address symptoms, with limited success in targeting the fundamental mechanisms. Berberine (BBR), a bioactive compound recognized for its anti-inflammatory, antioxidant, and anti-fibrotic characteristics, presents a compelling option for treating RISI.MethodsThe molecular targets of BBR and RISI were identified using Swiss Target Prediction and GeneCards databases. A protein-protein interaction (PPI) network was then constructed, and core targets were screened with the Cytoscape plug-in. Molecular functions and pathways were analyzed through GO and KEGG pathway enrichment analyses. Proteomic analysis identified differential protein expression following BBR treatment. Molecular docking validated BBR’s binding to core targets PRKACA and PIK3CB. Finally, the therapeutic efficacy of BBR was confirmed in irradiated cell and animal models.ResultsBBR is pivotal in modulating molecular pathways linked to inflammation, oxidative stress, and tissue repair. Protein histology indicates a marked increase in epithelial migration and proliferation markers (KRT14, KRT16) and a decrease in inflammatory markers (IL6ST, TNFRSF10B). Enrichment of pathways like the MAPK cascade and epithelial development highlights BBR’s role in skin regeneration. Molecular docking confirms BBR’s stable binding to key targets PRKACA and PIK3CB, essential for cell proliferation and inflammation control. Moreover, BBR treatment promoted the proliferation of irradiated cells and accelerated wound healing in irradiated animal models.ConclusionBerberine demonstrates multi-target therapeutic potential in managing RISI by modulating inflammation, oxidative stress, and cellular repair processes. These findings provide a foundation for future clinical studies to optimize its dosage and delivery, aiming to improve treatment outcomes for RISI.